A guide to the new language of accounting and finance - Hussey, Roger; Ong, Audra (Financial accounting and auditing collection., 2021)
The disciplines of accounting and finance have been rapidly changing in recent years. The methods and techniques being used have created a new language for managers, students, practitioners, academics. The Guide focuses specifically on the terms used in accounting and finance. Important terms and phrases are identified but with a much longer, in-depth explanation than you would normally find in a dictionary. Not only does each entry gives a thorough explanation of each term, it provides two or more references to academic articles that go into much greater depth. Hence, the entries give the reader immediate access to the literature.